Prevalence of peri‐implant disease and risk indicators in a Japanese population with at least 3 years in function—A multicentre retrospective study - Wada, Masahiro; Mameno, Tomoaki; Onodera, Yoshinobu; Matsuda, Hirofumi; Daimon, Koji; Ikebe, Kazunori (Clinical oral implants research, 2019)
Objectives The aim of this study was to evaluate the prevalence of peri‐implant disease and analyze risk indicators in Japanese subjects with ≥3 years of implant function. Material and methods Five hundred and forty‐three subjects treated with 1,613 implants were evaluated. Information was collected about the patients’ physical and dental history, as well as implant details. Peri‐implant evaluation included probing depth, bleeding on probing (BoP), suppuration (Sup), and keratinized tissue width. Bone loss was calculated from intra‐oral radiographs taken after 1 year and more than 3 years of function. Implants were classified into three groups: healthy, peri‐implant mucositis (BoP without bone loss), and peri‐implantitis (BoP and/or Sup with bone loss >1 mm). These data were analyzed by multivariable multinomial logistic regression. Results The prevalence of peri‐implant mucositis and peri‐implantitis at the subject level was 23.9% and 15.8%, respectively. An association was found between peri‐implant mucositis and plaque control record (PCR) >20% and keratinized tissue width <2 mm. Peri‐implantitis was associated with PCR >20%, smoking, insertion in the maxilla, and keratinized tissue width <2 mm. Conclusions Within the limitations of this study, the prevalence of peri‐implant diseases was elucidated in a Japanese population. Peri‐implant mucositis was associated with poor oral hygiene and less keratinized tissue. Poor oral hygiene, smoking, insertion in the maxilla, and less keratinized tissue were risk indicators for peri‐implantitis.